The role of RNA regulators, quorum sensing and c‐di‐GMP in bacterial biofilm formation - Manuel Condinho; Beatriz Carvalho; Adriana Cruz; Sandra N. Pinto; Cecília M. Arraiano; Vânia Pobre (FEBS Open Bio, 2023)
Biofilms provide an ecological advantage against many environmental stressors, such as pH and temperature, making it the most common life‐cycle stage for many bacteria. These protective characteristics make eradication of bacterial biofilms challenging. This is especially true in the health sector where biofilm formation on hospital or patient equipment, such as respirators, or catheters, can quickly become a source of anti‐microbial resistant strains. Biofilms are complex structures encased in a self‐produced polymeric matrix containing numerous components such as polysaccharides, proteins, signalling molecules, extracellular DNA and extracellular RNA. Biofilm formation is tightly controlled by several regulators, including quorum sensing (QS), cyclic diguanylate (c‐di‐GMP) and small non‐coding RNAs (sRNAs). These three regulators in particular are fundamental in all stages of biofilm formation; in addition, their pathways overlap, and the significance of their role is strain‐dependent. Currently, ribonucleases are also of interest for their potential role as biofilm regulators, and their relationships with QS, c‐di‐GMP and sRNAs have been investigated. This review article will focus on these four biofilm regulators (ribonucleases, QS, c‐di‐GMP and sRNAs) and the relationships between them.